Abstract characterization of a conditional expectation operator on the space of measurable sections - Ganiev, Inomjon G.; Hassan, Torla (Penerbit Universiti Kebangsaan Malaysia, 2017)
A conditional expectation operator plays an important role in geometry of Banach spaces. However, the main issue is with regards to the existence of a conditional expectation operator that permits other objects to be considered such as martingales and martingale convergence theorems. Thus, the purpose of this study is to provide an abstract characterization of a conditional expectation operator on a space of measurable sections.